Sosialisasi Peran Zakat Produktif Dalam Meningkatkan Kesejahteraan Ummat - Muhammad Arfan Harahap; Ahmad Daud; Sri Wahyuni Hasibuan (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Understanding related to productive zakat is still a phenomenon for the community in its implementation. An activity is needed that provides information related to the implementation of productive zakat to the community to support the achievement of productive zakat goals. Productive zakat is the utilization of zakat through innovation given to a person or group of people to be used as working capital or other forms. Giving productive zakat to mustahik is expected to help increase mustahik's income so that it can reduce poverty levels. The distribution of productive zakat is expected to be able to improve the welfare of the ummah by getting more benefits than just consuming the zakat received. The implementation of this community service activity was carried out in Telaga Said Village, Sei Lepan District, Langkat Regency with participants from the village community. This activity is one of the Tri Darma of higher education carried out by STAI Jam'iyah Mahmudiyah, Langkat in an effort to advance education specifically and the welfare of the community in general